PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) MATERI BARISAN UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP PESERTA DIDIK KELAS XI SMA - Wahyuni, Dilla (Jurnal Edukasi dan Penelitian Matematika, 2023)
Modules may be used to educate. School modules don't relate the information to the actual world and deliver the ideas and material straight. This may affect underdeveloped kids' arithmetic skills.  Therefore, developing valid, practical, and effective RME-based modules to increase students' concept comprehension.  The Plomp development model is used in this R&D. Preliminary research, prototyping, and evaluation are the research steps. The designed module was valid with an average of 86.79%, practical in the small group assessment stage with 81.59%, and practical at the field test stage with 81.41%. The field test showed that the curriculum improved SMA N 4 Bukittinggi students' concept comprehension.Keywords – Module, Realistic Mathematic Education, Concept Understanding, Plomp